2021
DOI: 10.3390/cells10102681
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Research Tools in Human Metabolic Disorders: An Overview

Abstract: Metabolic disorders are very common in the population worldwide and are among the diseases with the highest health utilization and costs per person. Despite the ongoing efforts to develop new treatments, currently, for many of these disorders, there are no approved therapies, resulting in a huge economic hit and tension for society. In this review, we recapitulate the recent advancements in stem cell (gene) therapy as potential tools for the long-term treatment of both inherited (lysosomal storage diseases) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 145 publications
0
3
0
1
Order By: Relevance
“…Inborn metabolic disorders encompass various types with complex metabolic defects, and a perfect classification method has yet to be established. Previous research has primarily focused on experimental studies of stem cell therapy for inborn metabolic disorders related to the connective tissue, musculoskeletal, neurological, and hematopoietic systems ( Ricci and Cacialli, 2021 ; Specchio et al, 2021 ). For instance, MSCs and their EVs have shown potential in treating corneal diseases caused by Mucopolysaccharidoses by delivering the enzyme N-acetylgalactosamine-6-sulfate sulfatase (GALNS) to defective cells ( Flanagan et al, 2021 ).…”
Section: Effects Of Different Cellular Microenvironments On Mscs' Sen...mentioning
confidence: 99%
“…Inborn metabolic disorders encompass various types with complex metabolic defects, and a perfect classification method has yet to be established. Previous research has primarily focused on experimental studies of stem cell therapy for inborn metabolic disorders related to the connective tissue, musculoskeletal, neurological, and hematopoietic systems ( Ricci and Cacialli, 2021 ; Specchio et al, 2021 ). For instance, MSCs and their EVs have shown potential in treating corneal diseases caused by Mucopolysaccharidoses by delivering the enzyme N-acetylgalactosamine-6-sulfate sulfatase (GALNS) to defective cells ( Flanagan et al, 2021 ).…”
Section: Effects Of Different Cellular Microenvironments On Mscs' Sen...mentioning
confidence: 99%
“…Nakil tekniklerindeki ve destekleyici bakım stratejilerindeki ilerlemeler, hayatta kalma oranlarında önemli gelişmelere olanak sağlamıştır 26 . Kanserler (örneğin lösemi ve lenfoma), kalp yetmezliği, sinir bozuklukları, otoimmün hastalıklar, metabolizma hastalıkları (örneğin diabetes mellitus, obezite ve osteoporoz) veya genetik bozukluklar (örneğin lizozomal depo hastalığı, peroksizomal hastalıklar ve mitokondriyal hastalıklar) gibi çeşitli hastalıkları tedavi etmek için kök hücre nakli gerçekleştirilmektedir 27,28 . Kök hücre nakil çeşitleri; kök hücre kaynağına göre (kemik iliği kök hücre nakli, periferik kan kök hücre nakli ve kordon kanı kök hücre nakli) veya donör tipine göre (otolog kök hücre nakli ve allojenik kök hücre nakli) veya hazırlama rejimine göre (miyeloablatif kök hücre nakli ve miyeloablatif olmayan kök hücre nakli) sınıflandırılabilir 5,29 .…”
Section: Kök Hücre Nakilleriunclassified
“…In the spinal cord, neurotrophins and receptors can modulate repair after a traumatic event [ 19 , 20 ]. Indeed, recent functional in vivo studies in mouse and rat models showed that cell transplants [ 21 ], including engineered stem cells (that overexpress neurotrophins and/or receptors), can affect the function of spinal neurons and circuits [ 22 ]. However, further studies using emerging animal models, such as the zebrafish ( Danio rerio ), could be useful to elucidate the specific mechanisms of this damage.…”
Section: Introductionmentioning
confidence: 99%